Palliative Performance Scale Score at 1 Week After Palliative Care Unit Admission is More Useful for Survival Prediction in Patients With Advanced Cancer in South Korea. (September 2018) - Yoon, Seok-Joon; Choi, Sung-Eun; LeBlanc, Thomas W.; Suh, Sang-Yeon
Background: The Palliative Performance Scale (PPS) is a useful prognostic index in palliative care. Changes in PPS score over time may add useful prognostic information beyond a single measurement. Objective: To investigate the usefulness of repeated PPS measurement to predict survival time of inpatients with advanced cancer admitted to a palliative care unit (PCU) in South Korea. Design: Prospective observational cohort study. Setting/Patients: 138 patients with advanced cancer admitted to a PCU in a university hospital in South Korea from June 2015 to May 2016. Measurements: The PPS score was measured on enrollment and after 1 week. We used Cox regression analyses to calculate hazard ratios (HRs) to demonstrate the relationship between survival time and the groups categorized by PPS and changes in PPS score, after adjusting for clinical variables. Results: There were significant differences in survival time among 3 groups stratified by PPS (10-20, 30-50, and≥ 60) after 1 week. A group with a PPS of 10 to 20 at 1 week had the highest risk (HR: 5.18 [95% confidence interval, 1.57-17.04]) for shortened survival. On the contrary, there were no significant differences among these groups by initial PPS alone. Similarly, change in PPS was prognostic; median survival was 13 (10.96-15.04) days for those whose PPS decreased after 1 week and 27 (10.18-43.82) days for those with stable or increased PPS ( P < .001). Conclusions: Measuring PPS over time can be very helpful for predicting survival in terminally ill patients with cancer, beyond a single PPS measure at PCU admission.